2014
DOI: 10.4238/2014.march.17.3
|View full text |Cite
|
Sign up to set email alerts
|

Dephosphorylation of NSSR1 regulates alternative splicing of the GluR-B minigene

Abstract: ABSTRACT. Neural salient serine/arginine-rich protein 1 (NSSR1, alternatively SRp38) is an important splicing factor that can repress pre-mRNA alternative splicing in cells during heat shock and mitosis. We show here that NSSR1 protein is dephosphorylated when cells are heat shocked or incubated with kinase inhibitor K252a. Both heat shock and K252a treatment increase the truncated splicing isoform of the GluR-B minigene pre-mRNA. We also investigated the roles of the RRM motif and three RS domains of NSSR1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The domain analysis of the four SR proteins indicates that RRM1/2 conferred splicing functions other than RNA binding, which is consistent with previous studies ( Zhang et al, 2014 ; Lee et al, 2017 ); and in the context of SMN1/2 exon 7 inclusion, they acted as splicing activators when bound to the upstream intron with only one exception of CP-RRM1 of SRSF9 that was neutral, whereas they acted as splicing repressors or had no effects when bound to the downstream intron.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The domain analysis of the four SR proteins indicates that RRM1/2 conferred splicing functions other than RNA binding, which is consistent with previous studies ( Zhang et al, 2014 ; Lee et al, 2017 ); and in the context of SMN1/2 exon 7 inclusion, they acted as splicing activators when bound to the upstream intron with only one exception of CP-RRM1 of SRSF9 that was neutral, whereas they acted as splicing repressors or had no effects when bound to the downstream intron.…”
Section: Resultssupporting
confidence: 89%
“…RS domains are thought to function in recruiting components of the basal splicing machinery through protein-protein interactions ( Phelan et al, 2012 ; Hertel & Graveley, 2005 ). However, splicing can be rescued by SR proteins in an RS domain-independent manner, indicating that RRMs can perform functions other than RNA binding in certain circumstances ( Zhang et al, 2014 ). In cell-free S-100 complementation assays, Zhu & Krainer (2000) showed that the RS domain of SRSF2 is dispensable for constitutively spliced substrates or some substrates with ESEs.…”
Section: Introductionmentioning
confidence: 99%
“…Transfecting a SRSF10∆RRM derivative did not affect GluR-B splicing, but deleting portions of the RS domains promoted skipping of both exons (Zhang et al 2014).…”
Section: Metabolismmentioning
confidence: 92%
“…5c) (Komatsu et al 1999). Using a minigene model in human PFSK-1 cells subjected to heat-shock, dSRSF10 was associated with a change in the alternative splicing of mutually exclusive flip/flop exons in the Glutamate receptor subunit B (GluR-B) (Zhang et al 2014). Overexpression of SRSF10 promotes flip exon inclusion but depleting SRSF10 in non-heat shock cells has no effect.…”
Section: Metabolismmentioning
confidence: 99%